Investigation of Raman fiber laser temperature probe based on fiber Bragg gratings for long-distance remote sensing applications - Lee, JH; Kim, J; Han, YG; Kim, SH; Lee, SB (OPTICAL SOC AMER, 2004)
We demonstrate a practical and simple, all fiber Bragg grating (FBG) based Raman laser sensing probe for long-distance, remote temperature sensing application. Using multiple laser cavities based on FBG's and a tunable chirped FBG, we obtain the simultaneous multichannel remote temperature sensing operation at a 50 km distance. The temperature sensitivity is measured to be 7.15 pm/degreesC. (C) 2004 Optical Society of America.
Keywords: SENSORS